Evaluation of B lymphocyte stimulator and a proliferation inducing ligand as candidate biomarkers in lupus nephritis based on clinical and histopathological outcome following induction therapy. Issue 1 (22nd January 2015) - Parodis, Ioannis; Zickert, Agneta; Sundelin, Birgitta; Axelsson, Magnus; Gerhardsson, Jakob; Svenungsson, Elisabet; Malmström, Vivianne; Gunnarsson, Iva
Abstract : Objectives: Lupus nephritis (LN) is a major cause of morbidity in patients with systemic lupus erythematosus (SLE). B cells have a central role in the pathogenesis of SLE. B lymphocyte stimulator (BLyS) and a proliferation inducing ligand (APRIL) are pivotal in B cell homeostasis. We aimed to investigate a potential role of serum BLyS and APRIL as biomarkers in LN, especially as predictors of treatment response. Methods: Sixty-four patients with active LN (52 proliferative lupus nephritis (PLN); 12 membranous LN) were included. Renal biopsies were performed at baseline and after immunosuppressive treatment. Serum levels of BLyS, APRIL and autoantibodies were measured on both biopsy occasions and in 64 individually matched controls. Renal biopsies were evaluated using the International Society of Nephrology/Renal Pathology Society classification, and scored for Activity Index and Chronicity Index. Clinical responders (CR) were required to have ≥50% reduction in proteinuria, normal or improved renal function, and inactive urinary sediment. Histopathological responders (HR) were required to have ≥50% improvement in Activity Index. Results: Baseline BLyS levels were significantly higher in LN patients compared with controls (p<0.001) and remained unchanged following induction treatment. APRIL levels were significantly higher in patients compared with controls at baseline (p=0.005) and decreased following treatment (p<0.001). Among PLN patients, APRIL levels decreased significantly only in responders (CR: p=0.009; HR: p=0.01). Baseline BLyS levels <1.5 ng/mL predicted treatment response, attaining a positive predictive value of 92% for CR with PLN at baseline. Conclusions: BLyS and APRIL were affected differently by immunosuppression; BLyS levels remained unchanged following therapy while APRIL levels decreased. Despite unchanged BLyS levels following therapy, low baseline levels predicted both clinical and histopathological improvement. Our data support APRIL as a candidate biomarker of renal disease activity in lupus patients with proliferative glomerulonephritis and point to low baseline BLyS levels predicting treatment response in LN, especially in PLN.